Strategi Kepemimpinan Kepala Sekolah Dalam Implementasi Pendidikan Karakter Berbasis Nilai Lokal - Agustina Rahmi; Siti Hanifah Husnul Khotimah; Dwi Sogi Sri Redjeki; Sabariah Sabariah (Wahana, 2024)
The skills of school principals in implementing character education in schools are very important. However, unfortunately it is still difficult to integrate character education into the curriculum, limited teacher abilities, and minimal parental involvement. The aim of this research is to explore the principal's leadership strategy in implementing local values-based character education at SMAN 3 Banjarbaru, how it is implemented, and identifying inhibiting factors and the solutions offered. This research uses qualitative methods with data collection techniques including observation, interviews and documentation. The research results show the leadership strategy of the principal of SMAN 3 Banjarbaru, namely: a) establishing a vision, mission, goals and incorporating local values ​​in learning, b) carrying out mentoring, evaluation and follow-up, c) establishing appropriate strategies, policies and programs, d) guiding and directing, and f) setting an example. Meanwhile, the implementation of the school principal's leadership strategy, by: a) incorporating local values ​​in learning, b) in schools carrying out habituation and acculturation of protecting the environment and cultivating a spiritual soul, c) carrying out mentoring, evaluation and carrying out follow-up, e) opening space for discussion and f) determine strategies and programs based on student needs. The solution taken by the school principal if there are challenges and obstacles is by: ensuring the implementation of character education in the classroom and outside the classroom, identifying problems, and carrying out follow-up actions.